Co-exposure to lead and cadmium is associated with increased severity of social deficits in children with autism spectrum disorders - Mao, Hongjie; Qian, Yifang; Su, Yanling; Liu, Xiumei; Nie, Xiuzhen; Cai, Yingying (Frontiers in Nutrition, 2026)
ObjectiveThis case–control study aimed to compare micronutrient (vitamins and minerals) profiles between children with autism spectrum disorders (ASD) and age- and gender-matched typically developing (TD) controls. It further sought to explore the associations of these profiles with core symptom severity and neurodevelopmental outcomes in ASD.MethodsWe enrolled 50 children with ASD and 50 matched TD controls. Core ASD symptoms were assessed using the Autism Diagnostic Observation Schedule-Second Edition (ADOS-2) and Childhood Autism Rating Scale (CARS), while neurodevelopmental status was evaluated with the Gesell Developmental Scale (GDS). Serum vitamin and mineral levels were measured in all participants. Eating behaviors were assessed using the Preschooler’s Eating Behavior Questionnaire (PEBQ).ResultsKey findings included: (1) significantly more severe eating behavior disturbances in ASD children, characterized by increased food selectivity, reduced self-feeding ability, and maladaptive eating patterns; (2) markedly higher serum iron levels in the ASD group (p = 0.028); (3) elevated serum lead (Pb) and cadmium (Cd) levels were positively correlated with social communication impairments. Notably, a combined heavy metal exposure index (reflecting Pb-Cd co-exposure) remained significantly associated with these impairments after controlling for screen time; (4) higher serum levels of vitamins D and B12 were associated with better gross motor development, whereas increased copper (Cu) levels were inversely associated with motor function. Elevated calcium (Ca) levels were positively associated with adaptive behavior development.ConclusionThese results demonstrate that both nutritional imbalances and co-exposure to heavy metals such as lead and cadmium are significantly associated with behavioral symptoms and neurodevelopmental outcomes in ASD. The findings underscore the importance of integrating routine nutritional surveillance and assessment of environmental heavy metal exposure to guide personalized interventions in this population. These cross-sectional associations warrant further investigation in larger, longitudinal studies that incorporate detailed dietary and environmental assessments to explore potential causal mechanisms.